ANALISIS SINEMATOGRAFI PROGRAM SITKOM KERABAT KERJA EPISODE 7 LPP TVRI SUMATERA BARAT - Tommy Chaniago; Andri Maijar (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem in this thesis is the Cinematography Analysis of the Kerabat Kerja Sitcom Program Episode 7 on LPP TVRI West Sumatra. The purpose of this research is to understand how cinematography elements are applied in the Kerabat Kerja Sitcom Program Episode 7 on LPP TVRI West Sumatra. This research was conducted on the Kerabat Kerja Sitcom Program Episode 7 on LPP TVRI West Sumatra. The type of this research is qualitative research using a descriptive qualitative approach. The instrument in this research is the researcher itself. The data collection methods used by the author are observation, interviews, and documentation. Based on the research results, there are several cinematography elements used in the Kerabat Kerja Sitcom Program Episode 7 on LPP TVRI West Sumatra, namely shot sizes: long shot, medium shot, medium close-up, and close-up; Camera placement: camera point of view; Camera movements: zoom in, pan left, tilt down, and follow; Recording style: the concept of the developing shot; Camera angles: high angle, normal angle, and low angle; Composition: headroom, noseroom, looking space, and over the shoulder shot; Continuity: continuity of direction, continuity of color, continuity of action, and continuity of location; Lighting arrangement: key light, fill light, and back light; Editing: continuity editing.